2017
DOI: 10.18632/oncotarget.18581
|View full text |Cite
|
Sign up to set email alerts
|

The application of enhanced recovery after surgery (ERAS)/fast-track surgery in gastrectomy for gastric cancer: a systematic review and meta-analysis

Abstract: BackgroundThe study aimed to compare the safety and effectiveness of Enhanced recovery after surgery (ERAS) with conventional care in gastrectomy for gastric cancer.MethodsSearch strategy from Pubmed, Embase, Web of science, Cochrane library and reference lists was performed. The collected studies were randomized controlled trials and published only in English, and undergoing ERAS in gastrectomy for gastric cancer from January 1994 to August 2016.ResultsA total of eight studies including 801 patients were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
54
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 47 publications
3
54
2
3
Order By: Relevance
“…[23][24][25] However, some studies have raised the concern that early discharge could miss complications and lead to a higher readmission rate. 26,27 Complication rates (13.4%) within 30 days after surgery were comparable to previous conventional studies (13.0%-16.6%) 5,6 and our conventional CP group (9.5%, P = 0.338). The readmission rate (6.3%) in this study was also comparable to previous studies that applied conventional management (3.8%-7.5%), [28][29][30] although it was higher than that of our conventional CP group (0.7%).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…[23][24][25] However, some studies have raised the concern that early discharge could miss complications and lead to a higher readmission rate. 26,27 Complication rates (13.4%) within 30 days after surgery were comparable to previous conventional studies (13.0%-16.6%) 5,6 and our conventional CP group (9.5%, P = 0.338). The readmission rate (6.3%) in this study was also comparable to previous studies that applied conventional management (3.8%-7.5%), [28][29][30] although it was higher than that of our conventional CP group (0.7%).…”
Section: Discussionsupporting
confidence: 85%
“…The mean length of hospital stay (4.7 ± 1.3 days) was shorter than our historical cohort that had completed a conventional CP (7.2 ± 2.3 days) and the previous time periods reported for gastric cancer ERAS (6.8 − 9.0 days) . However, some studies have raised the concern that early discharge could miss complications and lead to a higher readmission rate …”
Section: Discussioncontrasting
confidence: 51%
“…Our findings demonstrate that the ERAS program resulted in shorter length of hospital stay (LOS), reduced hospital costs, reduced time to return of gut function, without compromising on risks of morbidity and mortality; however, an increased rate of readmission was observed in the ERAS arm, a finding not demonstrated in previous meta-analyses. Furthermore, there were weaknesses in these studies [35][36][37][38][39][40][41][42][43]. All except one meta-analysis [38] included only randomized controlled trials (RCTs); Li et al [37] only examined laparoscopic gastrectomy; Ding et al [36] limited their analysis to English language articles.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons were equally as likely to utilise early oral intake in total gastrectomy and Ivor Lewis oesophagectomy procedures (Table ). Early oral intake has been successfully utilised in various fields of surgery such as colorectal surgery and its use in upper gastrointestinal surgery is growing . A recent meta‐analysis investigating the impact of fast‐track protocols in upper gastrointestinal surgery found that early oral feeding significantly reduced postoperative morbidity, postoperative hospitalisation and overall costs, without an increase in readmission, reoperation or mortality rates …”
Section: Discussionmentioning
confidence: 99%
“…Early oral intake has been successfully utilised in various fields of surgery such as colorectal surgery and its use in upper gastrointestinal surgery is growing. 20,21 A recent meta-analysis investigating the impact of fast-track protocols in upper gastrointestinal surgery found that early oral feeding significantly reduced postoperative morbidity, postoperative hospitalisation and overall costs, without an increase in readmission, reoperation or mortality rates. 22 It must be taken into account though, that following major upper gastrointestinal surgery, patients may not achieve nutritional targets through oral intake alone, necessitating the introduction of alternate nutritional support methods such as nasoenteric feeding or TPN.…”
Section: Discussionmentioning
confidence: 99%